The spark of time: Nietzsche, history, and memory - Nogueira Pereira, Rafael Gomes (Sofia, 2026)
In this article, we examine Nietzsche’s critique of the rationalization of historical knowledge in the nineteenth century. The guiding hypothesis of this analysis is that Nietzsche’s critiques of historical knowledge should be understood through their entanglement with the problem of memory, insofar as the scientifization of the past promotes an excessive accumulation of memory and leads to the paralysis of existential potentialities. We further argue that Nietzsche’s critique can be better understood when situated in dialogue with Arthur Schopenhauer’s contribution, particularly through his work, The World as Will and Representation. Accordingly, we explore the interrelation between Nietzsche and Schopenhauer as a means of more precisely elucidating the Nietzschean perspective.
Keywords: history; memory; Schopenhauer